Utilization of Surplus Air Thermal Energy by a Water Cycle System in a Chinese-Type Solar Greenhouse - Lu Wang; Yiming Li; Zhouping Sun; Sida Meng; Tianlai Li; Xingan Liu (Agronomy, 2024)
Solar greenhouses are commonly overheated during the day, and the remaining air heat can only be dissipated through ventilation, which is a severe energy waste problem. In order to improve the energy utilization of the greenhouse, this study proposes a water cycle system using surplus air thermal energy, which consists of an air-water heat exchanger, supply and return pipes, a submersible pump, a water tank, and an automatic control system. The proposed system stores the surplus air thermal energy in the greenhouse in the water tank. It releases it into the greenhouse using water circulation, and experimental analyses were carried out using a solar greenhouse in the Shenyang area. The effects of different air and water flow rates on the performance of the surplus air thermal energy water recycling system and the environment inside the greenhouse were analyzed by establishing a CFD model and model validation, and the average difference between the experimental data and the simulated data was 6.98%. The results show that the circulating air flow rate significantly affects the system performance and the environment inside the greenhouse. In the heat collection stage, the water circulation system with an airflow rate of 9 m/s has a minor average temperature difference in the vertical plane of the greenhouse. The water circulation system with an airflow rate of 6.0 m/s collects and releases the most significant heat. The temperature cloud between the vertical and horizontal planes is more uniform. This research provides new ideas for efficient energy use in solar greenhouses.